(untitled) (Diametros, 2015)
The use of assisted reproductive technology (ART) is becoming more and more common nowadays and the procedures that a few years ago would be seen as experimental have now become basic benefits. The present text covers the issues of risks and conflicts faced by family members and related with the use of technology in the process of conceiving and giving birth to a child. The authors pay special attention to the possible use of foreign germ cells in the conception of a child. The article aims to demonstrate that the use of modern and advanced medical technology in health care in the field of medically assisted procreation may be seen as a benefit for the family, which satisfies the desire to have a child, but in the long run it may give rise to legal or psychological problems as well. The authors examine the draft on the infertility treatment